THE EFFECT OF PUPPET SHOW ON HOSPITALIZATION IN PRESCHOOL CHILDREN (3-6 YEARS) - Sulpat, Emuliana; Mardhika, Amellia; Fadliyah, Lailatul; Tyas, Anestasia Pangestu Mei; Harianto, Susilo; Ilhami, Yusrina Ika (Journal of Vocational Nursing, 2022)
Introduction: One way to minimize the impact of hospitalization is storytelling with dolls or puppet shows , which is a type of game using puppet media through fantasy games for preschoolers (3-6 years old). The purpose of this study was to determine the effect of play therapy "puppet show" on the impact of hospitalization on preschool children (3-6 years) in the Orchid room of Ibnu Sina Hospital, Gresik Regency. Methods: This study uses a quasi experiment with one group pre test and post test design. The population of this research is parents who have preschool age children (3-6 years) who are hospitalized in the Orchid Room of Ibnu Sina Hospital, Gresik Regency. While the sampling using consecutive sampling technique obtained 22 parents. The independent variable studied was play therapy "puppet show". The dependent variable in this study was the impact of hospitalization on preschool children aged (3-6 years) who experienced hospitalization. Data collection is done by using a questionnaire then analyzed through the T-test statistical test. Results: The results of this study indicate that there is a significant difference between positive and negative impacts on pre-school age children during nursing actions before and after play therapy "puppet show" (p value = 0.005 smaller than = 0.05). Conclusions: Based on the results of the research obtained, the need for play should still be given to children undergoing hospital treatment to continue the child's growth and development, reduce stress and tension.